2018
DOI: 10.5152/ejbh.2018.3757
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Health Literacy with Breast Cancer Knowledge, Perception and Screening Behavior

Abstract: Interventions to enhance breast cancer knowledge and screening should notice the HL of women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
0
35
1
2
Order By: Relevance
“…Social networks can influence individuals' behavior by circulating information and beliefs on the effectiveness of recommended health behavior (Berkman and Glass, 2000). Beliefs and knowledge about breast cancer screening have been shown to be key determinants of mammography utilization (Dündar et al, 2006;Ferrat et al, 2013;Grunfeld et al, 2002;Lagerlund et al, 2000;Rakhshkhorshid et al, 2018). In addition, evidence shows that social network measured as the number of contact with family and friends as well as emotional social support (i.e., having someone to discuss personal concerns with) have a positive influence on mammography participation (Jensen et al, 2015).…”
Section: Theoretical Considerations and Relevant Empirical Literaturementioning
confidence: 99%
“…Social networks can influence individuals' behavior by circulating information and beliefs on the effectiveness of recommended health behavior (Berkman and Glass, 2000). Beliefs and knowledge about breast cancer screening have been shown to be key determinants of mammography utilization (Dündar et al, 2006;Ferrat et al, 2013;Grunfeld et al, 2002;Lagerlund et al, 2000;Rakhshkhorshid et al, 2018). In addition, evidence shows that social network measured as the number of contact with family and friends as well as emotional social support (i.e., having someone to discuss personal concerns with) have a positive influence on mammography participation (Jensen et al, 2015).…”
Section: Theoretical Considerations and Relevant Empirical Literaturementioning
confidence: 99%
“…Smoking and alcohol consumption are risk factors for various cancers, including breast cancer [48]. Past research reported a positive association between high breast cancer knowledge and breast cancer screening participation, and suggested individuals might undergo breast cancer screening if they are knowledgeable about breast cancer, such as risk factors, usefulness of mammography, or causes [17,49,50]. In addition, individuals who are interested in preventing health problems or who actively engage in preventive health behaviors would be likely to engage more in healthy behaviors that can reduce the risk of disease or death.…”
Section: Relationships Between Health Behaviors and Breast Cancer Scrmentioning
confidence: 99%
“…Previous studies have revealed that breast cancer screening participation is associated with healthrelated lifestyle and behavioral factors; such as knowledge or health literacy of breast cancer [15][16][17], smoking habit [18,19], alcohol consumption [19,20], physical activity level [21], and self-perceived health [20,22].…”
mentioning
confidence: 99%
“…Smoking and alcohol consumption are risk factors for various cancers, including breast cancer [48]. Past research has shown a positive association between high breast cancer knowledge and breast cancer screening participation, and suggested individuals might be more likely to undergo breast cancer screening if they are knowledgeable about breast cancer, including its risk factors, the usefulness of mammography, and causes [17,49,50]. In addition, individuals who are interested in preventing health problems or who actively engage in preventive health behaviors would be likely to engage more in healthy behaviors that can reduce the risk of disease or death.…”
Section: Relationship Between Health Behaviors and Breast Cancer Scrementioning
confidence: 99%
“…Previous studies have revealed that breast cancer screening participation is associated with healthrelated lifestyle and behavioral factors, such as knowledge or health literacy about breast cancer [15][16][17], smoking [18,19], alcohol consumption [19,20], physical activity level [21], and self-rated health (SRH) [20,22].…”
Section: Introductionmentioning
confidence: 99%